Optimization of Potassium Promoted Molybdenum Carbide Catalyst for the Low Temperature Reverse Water Gas Shift Reaction - James R. Morse; Cameron F. Holder; Jeffrey W. Baldwin; Heather D. Willauer (Energies, 2022)
The reduction of CO2 to CO through the reverse water gas shift (RWGS) reaction is an important catalytic step in the overall strategy of CO2 utilization. The product CO can be subsequently used as a feedstock for a variety of useful reactions, including the synthesis of fuels through the Fischer–Tropsch process. Recent works have demonstrated that potassium-promoted molybdenum carbide (K-Mo2C) is a highly selective catalyst for low-temperature RWGS. In this work, we describe the systematic investigation of key parameters in the synthesis of K-Mo2C, and their influence on the overall activity and selectivity for the low-temperature RWGS reaction. Specifically, we demonstrate how catalyst support, precursor calcination, catalyst loading, and long-term ambient storage influence performance of the K-Mo2C catalyst.